Spatio-Temporal Variations of Winter Phytoplankton Blooms Northwest of the Luzon Island in the South China Sea - Gao, Hui; Zhao, Hui; Han, Guoqi; Dong, Changming (Frontiers in Marine Science, 2021)
Phytoplankton is a key component of marine ecosystems. Winter phytoplankton blooms are frequently observed northwest of Luzon Island in the South China Sea. In this study, with the multi-satellite merged ocean color remote sensing data from November 1999 to February 2015, we examine the spatial and temporal changes of chlorophyll-a (Chl-a) concentration and further investigate its response to physical environment parameters including wind speed, Ekman transport, Ekman pumping velocity, sea surface temperature, and sea level anomalies in the region northwest of Luzon Island. The main factors affecting the distribution of Chl-a are discussed by using the partial correlation analysis and multiple stepwise linear regression analysis. The results show that centers of winter Chl-a blooms northwest of Luzon Island often occur near 119.5°E, 19.5°N. The significant multiple correlation (r = 0.76, p < 0.01) between Chl-a and oceanic conditions indicates that both the wind component parallel to the coastline and the wind stress curls enhance the winter upwelling in the study area, consistent with previous studies. A novel finding in the present study is that the winter bloom center is located north of the upwelling center, attributed to the advection effect of the northward background coastal flow.